Familial Waldenstrom’s macroglobulinemia and relation to immune defects, autoimmune diseases, and haematological malignancies – A population-based study from northern Sweden - Brandefors, Lena; Kimby, Eva; Lundqvist, Kristina; Melin, Beatrice; Lindh, Jack (Acta oncologica, 2016)
Waldenstrom's macroglobulinemia (WM) is a rare lymphoprolipherative disorder with geographic and ethnic disparities in incidence. The cause of WM remains mostly unknown although a role for genetic, immune-related, and environmental factors has been suggested. Most cases of WM are sporadic although familial cases occur. This study estimated the incidence of WM in northern Sweden and identified and described patients with familial WM in this area. The Swedish and Northern Lymphoma Registry, the Swedish Cancer Registry (1997-2011), and medical records were used to identify patients with WM in two counties (Norrbotten and Västerbotten) in northern Sweden and to calculate the overall age-adjusted incidence (2000-2012). We identified 12 families with a family history of WM, IgM monoclonal gammophathy (MGUS), and/or multiple myeloma (MM). In Norrbotten and Västerbotten, the age-adjusted incidence of WM/LPL is 1.75 and 1.48 per 100,000 persons per year, respectively (2000-2012), rates that are higher than the overall incidence of WM/LPL in Sweden (1.05 per 100,000 persons per year; 2000-2012). Autoimmune diseases and other haematological malignancies in the medical history (their own or in relatives) were reported in 9/12 and 5/12 families, respectively. A high proportion of abnormal serum protein electrophoresis was found in the relatives; 12/56 (21%) had a MGUS and 13/56 (25%) showed abnormalities in the immunoglobulin levels (i.e. subnormal levels and poly/oligoclonality). The incidence of WM in Norrbotten and Västerbotten counties was higher than expected. We found a strong correlation between autoimmune/inflammatory diseases, other haematological malignancies, and familial WM and a high frequency of serum immunoglobulin abnormalities in the relatives of the WM patients, findings that strengthen the hypothesis that the aetiology of WM depends on both immune-related and genetic factors.